2021
DOI: 10.1002/cre2.497
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of referrals from endodontic to orofacial pain specialists: A retrospective cohort study

Abstract: Objectives: Diagnosis and treatment of non-odontogenic pain is challenging for endodontists. The purpose of the study was to investigate the outcomes of referrals to orofacial pain specialists made for patients with suspected non-odontogenic pain, after evaluation and/or treatment by an endodontist. Materials and Methods:A retrospective review of dental records was conducted for 60 patients referred from a postgraduate endodontic clinic to an orofacial pain clinic.Patient demographics, pain history, endodontic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
(49 reference statements)
0
2
0
Order By: Relevance
“… 43 Further, no research has explored the association between mindfulness and pain-related outcomes in chronic orofacial pain. Given that orofacial pain conditions tend to be comorbid 44 , 45 and may share psychosocial processes, 43 assessing these coping variables in individuals with heterogeneous chronic orofacial pain may help develop interventions for this population that are scalable and implementable.…”
Section: Introductionmentioning
confidence: 99%
“… 43 Further, no research has explored the association between mindfulness and pain-related outcomes in chronic orofacial pain. Given that orofacial pain conditions tend to be comorbid 44 , 45 and may share psychosocial processes, 43 assessing these coping variables in individuals with heterogeneous chronic orofacial pain may help develop interventions for this population that are scalable and implementable.…”
Section: Introductionmentioning
confidence: 99%
“…The study concluded that it is difficult to diagnose and manage non-odontogenic pain. Patients may be more likely to experience persistent pain following endodontic therapy or suffer from an undetected, chronic orofacial pain disease as the genuine cause of their primary complaint 45 . Understanding the trigeminal system's pain neurobiology is essential to produce more effective and secure treatments.…”
Section: Collagenmentioning
confidence: 99%